Looking through and beyond conflicts: communal violence and the social orderin Hyderabad (India) - Mangiarotti, Emanuela (International journal of conflict and violence, 2019)
Communalism permeates the political, academic, media and everyday discourse in and about India. As a dominant interpretive framework, it expresses a particular politics of interfaith relations that normalises socio-political conflicts and violence intersecting with gender, class and caste relations. These intersections emerge in the experiences, practices and spaces of marginality and violence, revealing both the mechanisms of their normalisation in the context of communal violence and the experience of living within, through and despite it. Everyday life becomes the privileged context for reading communalism in light of a systematic reorganising of the gender-socio-economic governance, and the possibility to interrogate it. Based on an ethnographic study carried out in Hyderabad between 2009 and 2012, the paper reveals a politics of communal violence embedded in everyday social practices. It shows that the gender-socio-economic governance is not parallel to communalism but in fact constitutive of its logic and practices. The paper offers a perspective on how socio-political conflicts become actualised in a social order and how agency within such contexts unfolds as awareness of and action upon the space/possibility of their reconfiguration.